2010
DOI: 10.4103/0975-5950.79223
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dentigerous cysts in a nonsyndromic minor patient: Report of an unusual case

Abstract: A dentigerous cyst is an odontogenic cyst, thought to be of developmental origin. It is associated with the crown of an unerupted (or partially erupted) tooth. The cyst cavity is lined by epithelial cells derived from the reduced enamel epithelium of the tooth forming organ. Most dentigerous cysts are solitary. Multiple/bilateral cysts are usually found in association with a number of syndromes including cleidocranial dysplasia, Maroteaux-Lamy syndrome and Gorlin--Goltz syndrome (multiple OKCs). In the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
12
1
Order By: Relevance
“…17 That is an uncommon disorder characterized by numerous basal cell carcinomas, maxillary keratocysts and musculoskeletal malformations. 17,18 No microscopic and clinical features of this syndrome were found in the patients of the present case report.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…17 That is an uncommon disorder characterized by numerous basal cell carcinomas, maxillary keratocysts and musculoskeletal malformations. 17,18 No microscopic and clinical features of this syndrome were found in the patients of the present case report.…”
Section: Discussioncontrasting
confidence: 53%
“…Multiple DCs generally occur associated with syndromes such as mucopolysaccharidosis 7,8 and cleidocranial dysplasia. 5 Both these diseases cause modifications in tooth development and may take part in the occurrence of multiple DCs 17,18 Furthermore, multiple mandibular cysts have previously been reported after prolonged use of cyclosporine A and calcium channel blockers; 10 however, these are uncommon in the absence of a syndrome or systemic disease. 9 The patients analyzed in this case had no clinical or laboratory findings that could point towards syndromes or other systemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patient presented with impacted teeth, but she had not any swelling. In all reported cases, including the present case, radiographic examination showed a unilocular radiolucent lesion associated with the crown of an unerupted tooth with well-defined sclerotic margins (1,5). In addition to the developmental origin, some authors have suggested that periapical inflammation of non-vital deciduous teeth in proximity to the follicles of unerupted permanent teeth may be a factor for triggering dentigerous cyst formation (7).…”
Section: Discussionmentioning
confidence: 72%
“…Because CBCT provides reconstructed images of high diagnostic quality with lower exposure doses and shorter scanning time, compared to CT, CBCT was performed for this patient to give information about the lesion's extension, expansion of cortical plates, and the content and relationship of the lesion to adjacent anatomical structures, such as the inferior alveolar nerve (1,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation